Effects Of L-Carnitine Supplement On Plasma Coagulation And Anticoagulation Factors In Hemodialysis Patients - Fariba Hakeshzadeh; Hadi Tabibi; Minoo Ahmadinejad; Tahereh Malakoutian; Mehdi Hedayati (The Korean Society of Nephrology, 2012)
Hypercoagulability is an important risk factor for thrombosis and its complications in hemodialysis patients. This study was designed to investigate the effects of L-carnitine supplement on plasma coagulation and anticoagulation factors in hemodialysis patients. Methods: Thirty-six hemodialysis patients were randomly assigned to either a carnitine or a placebo group. Patients in the carnitine group received 1000 mg/day oral L-carnitine for12 weeks, whereas patients in the placebo group received a corresponding placebo. At baseline and the end of week12, 5 mL blood was collected after a 12- to 14-hour fast and plasma fibrinogen concentration, activity of plasma proteinC, coagulation factors V, VII, IX, and serum concentrations of tissue plasminogen activator (tPA), plasminogen activator inhibitor type-1 (PAI-1), free carnitine, and C-reactive protein (CRP) were measured. Results: In the carnitine group, mean serum free carnitine concentration increased significantly to 150% of baseline (p < 0.001), whereas plasma fibrinogen and serum CRP had 98 mg/dL (p < 0.01) and 41% (p < 0.01) significant decreases, respectively, at the end of week 12 compared with baseline. The reductions were significant compared with the placebo group (p < 0.05).No significant differences were observed between the two groups with regard to mean changes of the activity of plasma protein C, coagulation factors V, VII, IX, and serum PAI-1 to tPA ratio. Conclusion: L-Carnitine supplement reduces serum CRP, a marker of systemic inflammation, and plasma fibrinogen, an inflammation-related coagulation factor, in hemodialysis patients. Therefore, L-carnitine may play an effective role in preventing cardiovascular diseases in these patients.